Overview of Emotional Regulation of Teachers Assisting Students with Autistic Special Need - David R. Wardhana, Lauren; Suryanto, Suryanto (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
The issue addressed in this study is the importance of emotional regulation in the role of special assistant teachers when dealing with autistic students. This study aims to explore the emotional regulation experiences of special assistant teachers in managing students with autism. The participants consisted of three individuals—one male and two females—who met the criteria of working as special assistant teachers for more than one year. The study employed a qualitative descriptive case study approach. The findings indicate that emotional regulation among special assistant teachers tends to be positive. This is influenced by several factors, including emotional acceptance, the ability to engage in goal-directed behavior and refrain from impulsive actions when experiencing negative emotions, access to perceived effective emotional regulation strategies, and emotional awareness and understanding. The implication of these findings suggests that strengthening emotional regulation skills can be a key factor in supporting the effectiveness and psychological well-being of special assistant teachers in inclusive educational settings. Masalah yang diangkat dalam penelitian ini adalah pentingnya regulasi emosi dalam peran guru pendamping khusus saat menangani siswa autis. Penelitian ini bertujuan untuk mengetahui bagaimana gambaran regulasi emosi yang dialami oleh guru pendamping khusus dalam menangani siswa autis. Partisipan dalam penelitian ini berjumlah tiga orang, yang terdiri dari satu laki-laki dan dua perempuan dengan kriteria bekerja sebagai guru pendamping khusus dengan masa kerja rentang lebih dari 1 tahun. Pendekatan dalam penelitian ini menggunakan pendekatan kualitatif studi kasus deskriptif. Temuan penelitian menyebutkan regulasi emosi pada guru pendamping khusus cenderung ke arah yang positif. Hal tersebut dikarenakan oleh faktor-faktor seperti penerimaan emosi, kemampuan untuk terlibat dalam perilaku bertujuan, dan menahan diri dari perilaku implusif ketika mengalami emosi negatif, akses terhadap strategi regulasi emosi yang dipersepsikan efektif, serta kesadaran dan pemahaman tentang emosi. Implikasi dari temuan ini menunjukkan bahwa penguatan kemampuan regulasi emosi dapat menjadi aspek penting dalam mendukung efektivitas kerja guru pendamping khusus serta kesejahteraan psikologis mereka dalam lingkungan pendidikan inklusif.